SURFACE SEGREGATION OF SB IN DOPED TIO2 RUTILE - Gulino, A; Condorelli, G; Fragala, I; Egdell, R (1995)
The surface concentration of Sb in doped TiO2 rutile ceramics (Ti1 - 5 4xSbxO2 0 < x < 0.1), has been measured by means of angle-resolved core level X-ray photoelectron spectroscopy (AR-XPS). Depth profiles have been obtained by alternating Ar+-ion bombardment with core level measurements. At low doping levels Sb segregates by substitutional replacement of Ti in a large number of ionic planes whilst at higher Sb doping levels there is evidence of a new SbTiO amorphous surface phase whose thickness involves about five ionic planes. A rationalization of the monotonic decrease of the work function throughout the doping range studied has been proposed. © 1995.